Comment on "Spatio-temporal filling of missing points in geophysical data sets" by D. Kondrashov and M. Ghil, Nonlin. Processes Geophys., 13, 151–159, 2006 - T. Schneider (Nonlinear Processes in Geophysics, 2007)
No abstract available.